The retinal nerve fibre layer thickness in glaucomatous hydrophthalmic eyes assessed by scanning laser polarimetry with variable corneal compensation in comparison with age-matched healthy children - Hložánek, Martin; Ošmera, Jakub; Ležatková, Pavlína; Sedláčková, Petra; Filouš, Aleš (Acta ophthalmologica, 2012)
PURPOSE: To compare the thickness of the retinal nerve fibre layer (RNFL) in hydrophthalmic glaucomatous eyes in children with age-matched healthy controls using scanning laser polarimetry with variable corneal compensation (GDxVCC). METHODS: Twenty hydrophthalmic eyes of 20 patients with the mean age of 10.64 ± 3.02 years being treated for congenital or infantile glaucoma were included in the analysis. Evaluation of RNFL thickness measured by GDxVCC in standard Temporal-Superior-Nasal-Inferior-Temporal (TSNIT) parameters was performed. The results were compared to TSNIT values of an age-matched control group of 120 healthy children published recently as referential values. The correlation between horizontal corneal diameter and RNFL thickness in hydrophthalmic eyes was also investigated. RESULTS: The mean ± SD values in TSNIT Average, Superior Average, Inferior Average and TSNIT SD in hydrophthalmic eyes were 52.3 ± 11.4, 59.7 ± 17.1, 62.0 ± 15.6 and 20.0 ± 7.8 μm, respectively. All these values were significantly lower compared to referential TSNIT parameters of age-matched healthy eyes (p = 0.021, p = 0.001, p = 0.003 and p = 0.018, respectively). A substantial number of hydrophthalmic eyes laid below the level of 5% probability of normality in respective TSNIT parameters: 30% of the eyes in TSNIT average, 50% of the eyes in superior average, 30% of the eyes in inferior average and 45% of the eyes in TSNIT SD. No significant correlation between enlarged corneal diameter and RNFL thickness was found. CONCLUSIONS: The mean values of all standard TSNIT parameters assessed using GDxVCC in hydrophthalmic glaucomatous eyes in children were significantly lower in comparison with referential values of healthy age-matched children.
Keywords: Cross-Sectional Studies; nemoci zrakového nervu; Birefringence; mladiství; rohovka; Intraocular Pressure; Scanning Laser Polarimetry; nitrooční tlak; mužské pohlaví; Optic Nerve Diseases; průřezové studie; hydroftalmus; skenovací laserová polarimetrie; dítě; retinální gangliové buňky; Child; Retinal Ganglion Cells; ženské pohlaví; Humans; dvojitý lom; nervová vlákna; Nerve Fibers; Female; Adolescent; Cornea; lidé; Male; Hydrophthalmos